The controlled anniversary: Trujillo’s centenary in the face of the expansion of Leguiismo - Ccasani Condo, Miguel Ángel (2022)
This paper analyzes how the centenary of Trujillo (1920) developed during the first years of the Legislative government, where its notorious institutional reforms and the approach to the «Patria Nueva» conditioned its approach, course and reception. For this, it will be based on informative reports, journalistic comments and official speeches to understand the scope of the legal project in the festive proposal, public participation and interest in one hundred years of Trujillo’s independence. It is concluded that, although the influence of legality was indirect, aspects such as the renewal of its independence symbols and paternalism through the landowner were maintained.